Higher Temperature at Lower Elevation Sites Fails to Promote Acclimation or Adaptation to Heat Stress During Pollen Germination - Flores-Rentería, Lluvia; Whipple, Amy V.; Benally, Gilbert J.; Patterson, Adair; Canyon, Brandon; Gehring, Catherine A. (Frontiers in Plant Science, 2018)
High temperatures associated with climate change are expected to be detrimental for aspects of plant reproduction, such as pollen viability. We hypothesized that 1) higher peak temperatures predicted with climate change would have a minimal effect on pollen viability at dispersal and larger negative affects at germination, 2) high temperatures during pollen dispersal would facilitate acclimation to high temperatures during pollen germination, and 3) pollen from populations at sites with warmer average temperatures would be better adapted to high temperature peaks. We tested these hypotheses in Pinus edulis, a species with demonstrated sensitivity to climate change, using populations along an elevational gradient. We tested for acclimation to high temperatures by measuring pollen viability during dispersal and germination stages in pollen subjected to 30, 35 and 40 °C in a factorial design. We also characterized pollen phenology and measured pollen heat tolerance using trees from nine sites along a 200 m elevational gradient that varied 4 °C in temperature. We demonstrated that this gradient is biologically meaningful by evaluating variation in vegetation composition and P. edulis performance. Male reproduction was negatively affected by high temperatures, with stronger effects during pollen germination than pollen dispersal. Populations along the elevational gradient varied in pollen phenology, vegetation composition, plant water stress, nutrient availability and plant growth. In contrast to our hypothesis, pollen viability was highest in pinyons from mid-elevation sites rather than from lower elevation sites. We found no evidence of acclimation or adaptation of pollen to high temperatures. Maximal plant performance as measured by growth did not occur at the same elevation as maximal pollen viability. These results indicate that periods of high temperature negatively affected sexual reproduction, such that even high pollen production may not result in successful fertilization due to low germination. Acquired thermotolerance might not limit these impacts, but pinyon could avoid heat stress by phenological adjustment of pollen development. Higher pollen viability at the core of the distribution could be explained by an optimal combination of biotic and abiotic environmental factors. The disconnect between measures of growth and pollen production suggest that vigor metrics may not accurately estimate reproduction.